Adsorption competition study between chromate and phosphate from their solutions by total reflection X ray fluorescence spectrometry. (1st September 2020) - Piol, María Natalia; Acuña Alfonso, Andrea; Saralegui, Andrea; Vázquez, Cristina
Abstract : This paper explores the application of Total Reflection X‐Ray Fluorescence (TXRF) spectrometry for chromate (CrO4 2− ) and phosphate (PO4 3− ) determinations in synthetic solutions after their adsorption onto dolomite. The competition between both contaminants is also evaluated. Adsorption processes are considered an inexpensive, non‐contaminating alternative for retaining, on a selected substrate, a variety of pollutants present in different effluents. For a specific adsorbent, an important factor to be taking into account is the competition among different possible species. Variables such as concentration, temperature, ionic strength and pH were evaluated. Dolomite, a natural mineral based on calcium and magnesium carbonates, was employed as adsorbent. TXRF is an efficient, fast trace element analytical technique and requires only minimum specimen preparation, for that reason is suitable for this study. The experiments were carried out in batch systems; pH and ionic strength of the solution were measured and controlled. The results obtained in individual systems (phosphate‐dolomite or chromate‐dolomite) indicate a 70.5% for phosphate and 22.7% for chromate removal. The adjustment of the ionic strength had no influence on the removal of the anions. According to this study, the adsorption of chromate was reduced to 14% when the pH increased; this fact did not affect phosphate removal. The removal of both ions increased at pH under than 6. The presence of both ions at different concentrations did not change the removal value for the phosphate, whereas the removal of chromate was almost null, indicating a strong interference of the phosphate in the removal of chromate.